Developing safer online environments for children tools and policies for combatting cyber aggression (Trending Topics Book Series (TTBS) Book Series, 2020)
"This book explores the effects of cyberbullying and cyberstalking on children and examines solutions that can identify and prevent online harassment through both policy and legislation reform and technological tools"--Provided by publisher.